ANTIBACTERIAL ACTIVITY OF CHLOROGENIC ACID PHYTOVESICLES AGAINST RESISTANT BACTERIA: DEVELOPMENT, OPTIMIZATION AND EVALUATION - TRIVEDI, HEMANGI; PURANIK, PRASHANT K. (International Journal of Applied Pharmaceutics, 2022)
Objective: To investigate the in vitro antibacterial activity of a naturally occurring polyphenol chlorogenic acid (CGA) and compares it with formulated chlorogenic acid phytovesicles against 4 different bacterial strains; two gram positive [Staphylococcous aureus and Bacillus subtilis] and two gram negative strains [Klebsiella pneumonia and Escherichia coli]. Methods: CGA phytovesicles were developed and optimized using central composite design to improvise CGA’s physicochemical properties. Bactericidal activity was evaluated using agar diffusion, minimum inhibitory concentration (MIC) and time kill assay. The effect of pH and temperature on the antimicrobial activity was determined. Results: The optimized CGA phytovesicles showed entrapment of 96.89% with 30 times better lipophilic solubility than the plain drug. The inhibition zone sizes for CGA phytovesicle ranged from 17-25 mm as compared to 15-20 mm of plain CGA while the MIC values ranged 200-250 µg/ml as compared to 500-550 µg/ml of plain CGA. CGA phytovesicles exhibited a strong bactericidal effect at MIC with a log reduction in the range of 0.90-2.04 in Colony forming units (CFUs) at 24h for different strains as compared to 1.38-2.17 of plain CGA. Furthermore, the antibacterial effect was found to augment with increasing temperature but decreased with alkaline pH. Conclusion: Results strongly supports the hypothesis of potential use of CGA phytovesicles as a mode of drug delivery for its antibacterial use against different resistant bacteria.